Implementation of Daily Physical Activity (DPA) in Indonesian Elementary Schools: Challenges and Opportunities - Zainuddin, M Said; Usman, Arifuddin; Iskandar, Iskandar; Badaru, Benny; Awaluddin, Awaluddin (Jurnal Pendidikan, Kesehatan dan Olahraga, 2025)
Despite established evidence supporting the benefits of physical activity for children's development, Indonesian elementary schools face significant challenges in implementing effective Daily Physical Activity (DPA) programs. This paper examines the implementation of DPA in Indonesian elementary schools through a comprehensive literature review and qualitative analysis of policy documents, academic research, and case studies. Research reveals that limited resources, insufficient systemic support, and increasingly sedentary lifestyles among students present major obstacles to DPA implementation. However, opportunities exist through government health policies, teacher innovation, community partnerships, and technology integration. The study proposes strategic interventions including enhanced teacher training, curriculum integration of physical activities, incentive systems, supportive school environment design, and multi-stakeholder partnerships. Findings indicate that successful DPA implementation requires coordinated efforts among schools, families, communities, and government to create sustainable programs that increase student physical activity beyond formal physical education classes. This research contributes valuable insights for education policymakers and practitioners seeking to improve children's health outcomes through school-based physical activity initiatives.